Effect of boriding time on the effective thermal diffusivity of the borided AISI 1018 steel - Yesenia Sánchez-Fuentes; Luz Alejandra Linares-Duarte; José Abraham Balderas-López; José Guadalupe Miranda-Hernández; Raúl Tadeo-Rosas; Cintia Proa-Coronado; Enrique Hernández-Sánchez (Scientific Reports)
Abstract Boriding is a thermochemical process by which the surface of metallic materials is strongly improved for many applications. When boriding is applied to ferrous alloys, a boride layer containing mainly a single-phase Fe $$_{2}$$ B or a double-phase Fe $$_{2}$$ B/FeB grows on the metallic substrate. The thickness of the boride layers depends primarily on the temperature and the treatment time. On the other hand, the thermal diffusivity is related to the materials’ density and thermal conductivity. Therefore, as the thickness of the boride layers increases, their density decreases, and so does their thermal diffusivity. In this work, the change in thermal diffusivity of the layered material, as a function of thermochemical treatment, is assessed. Samples of AISI 1018 steel were exposed to boriding treatment during 2, 4, 6, and 8 h at a constant temperature of 950 $$^°$$ C. The crystalline structure of the layers was analyzed by X-ray diffraction and optical microscopy. The mechanical properties and the thermal diffusivity of the steel-boride layered materials were evaluated by Vickers micro indentation and Photothermal Spectroscopy, respectively.